2022
DOI: 10.5603/cj.a2021.0158
|View full text |Cite
|
Sign up to set email alerts
|

NOAC versus warfarin in the treatment of atrial fibrillation during the first three months after bioprosthetic aortic valve replacement

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Cardiology Journal" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
4
0
3
Order By: Relevance
“…Tables 5 and 6 show the characteristics and results of the studies. The preliminary results of the observational studies were confirmed in several RCTs [11][12][13].…”
Section: Noacs Vs Vkas In Af Patients With Bhvs Replacementmentioning
confidence: 61%
See 2 more Smart Citations
“…Tables 5 and 6 show the characteristics and results of the studies. The preliminary results of the observational studies were confirmed in several RCTs [11][12][13].…”
Section: Noacs Vs Vkas In Af Patients With Bhvs Replacementmentioning
confidence: 61%
“…In a recent small trial [12], 50 AF patients undergoing aortic BHV replacement were randomized to receive apixaban (n = 25 patients) or warfarin (n = 25 patients) in a 1:1 ratio for the first 3 months after surgery. At 3 months follow-up, no valvular dysfunction was recorded; major bleeding events occurred in 3 patients (12%) among the warfarin group and none in the apixaban group.…”
Section: Noacs Vs Vkas In Af Patients With Bhvs Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of bioprosthetic valves has been steadily increasing, even in relatively young patients, considering the benefits of avoiding lifelong anticoagulation therapy and subsequent lifestyle modifications. Because the age of patients using bioprostheses is decreasing and patients tend to live longer, the durability of the bioprosthetic valve has become a significant goal to achieve [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, a segurança e tolerabilidade das novas terapias anticoagulantes orais são aspectos críticos a serem considerados na prática clínica. Embora ofereçam benefícios significativos em termos de redução do risco de sangramento intracraniano e gastrointestinal, é essencial uma abordagem cuidadosa, com monitorização regular da função renal e hepática, e estratégias de reversão disponíveis para garantir a segurança e eficácia desses agentes na prevenção de eventos cardiovasculares em pacientes com fibrilação atrial (Piepiorka-Broniecka et al, 2022).…”
Section: Segurança E Tolerabilidade Das Novas Terapias Anticoagulante...unclassified